Bioindication of anthropogenic eutrophication of water resources in Mogilev region - Sysa, Aliaksei Ryhor; Derzhanskaya, Anastasia Victorovna (Journal of the Belarusian State University. Ecology, 2020)
The aim of research is a comprehensive assessment of phyto- and zooplankton as a bioindication object in water resources of the Dnieper basin under various types of natural and anthropogenic effects. Object of study: rivers flowing on the territory of the Mogilev region - Berezina (Bobruisk district), which is the right tributary of Dnieper, and Olsa (Klichev district), which is the left tributary of Berezina. The subject of the study is single-cell photosynthetic protozoa, algae and invertebrates, which are sensitive to various types of pollution and can be used as bioindicators for the eutrophication of water bodies. The structural analysis of phyto- and zooplankton was carried out, species-indicators of saprobity of reservoirs among photosynthetic organisms and invertebrates were identified. A comparative analysis of the data obtained by bioindication with the data of hydrochemical parameters of the district center of hygiene and epidemiology was also carried out. It is shown that bioindication methods are not inferior in informativeness to hydrochemical methods and can also be widely used in studying the sanitary state of the surface waters of ecosystems, as well as being actively used in laboratory practice.
Keywords: quality of water; pollution; organisms-indicators; phytoplankton; zooplankton; eutrophanium; bioindication